Kepuasan Diskonfirmasi Warga pada Sektor Publik: Kasus Pelayanan Kebutuhan Dasar Pemerintahan Kota Padangpanjang - Lanin, Dasman; Mabarak, Adil (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2010)
Although public services are the right of the people orÂ citizens that must be met government, it seems still far from standard. This study tried to describe the image-disconfirmation of citizen satisfaction in public sector services in Padangpanjang in the area of basic needs (education, health and social). This variable would be viewed on the the aspects of age, gender, marital status, education, religious affiliation of citizens, Â ethnicity, revenue, economic status, political affiliation of citizens, and the relationship each of these aspects with the disconfirmation-satisfaction. A quantitative approach has been used in this study. Kata Kunci: Pelayanan publik, diskonfirmasi, kepuasan warga, sektor publik.